Unit of falls: a possibility of prevention falls in elderly - Battistella, Linamara Rizzo; Alfieri, Fábio Marcon (Acta Fisiátrica, 2011)
Falls are a public health problem for the elderly. Since the population is aging rapidly, interventions are needed in this situation. The pur-pose of this overview was to report on an example from the Falls Unit of the Mutual University Hospital of Terrassa in Barcelona, Spain. This unit evaluates and does orientations on risk factors of falling, carries on exercise programs for individuals with histories of falling, as well as for those at risk. We believe that programs like this, which have opera-tional viability, are necessary and must be incorporated into hospitals and health centers in order to diminish falls and their consequences.